Production diseases in farm animals: A comprehensive and illustrated clinical, laboratory, and pathological overview - Mohamed Tharwat; Abdulrahman A. Alkheraif; Shin Oikawa (Open Veterinary Journal)
The rising demand of the rapidly growing global population for animal-derived foods and other products requires intense animal farming. However, the husbandry and breeding of livestock are associated with a conflict between the economic requirements of producers and the biological needs of the animals. This conflict is rapidly gaining recognition not only by veterinarians, animal scientists, and producers but also by the general public. Any defect in animal feeding, housing, or breeding strategy may trigger the development of production diseases (PD), leading to decreased producer income, reduced consumer product quality, and impaired animal welfare. Because of the need for high production during the past decades, several animals have been subjected to intense genetic selection, thus increasing animal productivity to a standard where the requirement for nutrients from the ration and internal tissue stores has greatly increased. Therefore, the inability to address the high metabolic needs of increased production is also elevated. In farm animals, high production is greatly challenged by various risk factors, such as improper nutrition, infection, stress, and housing systems. Thus, new data concerning understanding the physiology, detection, treatment, and prevention of PD are urgently required. This review highlights the most important PDs that may influence different livestock species, including cows, sheep, camels, and goats. Recently, PD has been widened to include other conditions, such as fatty infiltration of the liver, sub-acute ruminal acidosis, hepatic abscess, caudal vena cava thrombosis, endocarditis, abomasal ulcerations, displacement of the abomasum, pregnancy toxemia, and mastitis. Because many PDs emerge during the transition period, the first section of this review focuses on a series of physiological events that occur during this period. Following, different partial discharge including will be discussed. [Open Vet J 2025; 15(1.000): 18-34]